2012
DOI: 10.4317/jced.50824
|View full text |Cite
|
Sign up to set email alerts
|

Oral squamous cell carcinoma among Yemenis: Onset in young age and presentation at advanced stage

Abstract: Objectives: Oral cancer represents a health burden worldwide. Up to 90% of oral cancer cases are squamous cell carcinomas (SCC). The data on oral SCC in Yemen are lacking. The objective of this study therefore was to describe and analyze the demographic, clinical and histological characteristics of Yemeni patients with oral SCC. Study Design: In this cross-sectional study, two sets of retrospective data for Yemeni cancer patients were obtained officially by two different registries. Patients with oral SCC were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…The prevalence is reported to be high in Southeast Asia, with figures higher than 30% of all malignancies 28. The male-to-female ratio of 1:1.9 is in agreement with earlier studies of KSA3,4 but differs most other reports, where it is predominant in males 17,29,30…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence is reported to be high in Southeast Asia, with figures higher than 30% of all malignancies 28. The male-to-female ratio of 1:1.9 is in agreement with earlier studies of KSA3,4 but differs most other reports, where it is predominant in males 17,29,30…”
Section: Discussionsupporting
confidence: 90%
“…Twenty-six percentage of OSCC patients were younger than 45 years in our study, which was comparable to findings in Yemen (24), but higher than those reported in Jordan (15), Brazil (11), Thailand (23), the United States (28), and the United Kingdom (29). The diagnosis of cancer at a younger age indicates the need to biopsy suspicious oral lesions to rule out malignancy in patients as young as in their second or third decade of life.…”
Section: Discussionsupporting
confidence: 85%
“…In our series, 14.3% of OSCC were below 40 years. Comparable results were reported in Yemen (14%) (24), Iran (13%) (22), and Libya (15%) (12). A lower proportion of younger cases of OSCC were seen in Brazil (8.7%) (11), Sri Lanka (8.7%) (19), and Malaysia (4.3%) (16).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations